Video7: An Architecture for Storage and Recovery of Streaming Audio and Video in NoSQL Database - Sampaio, Vanderson S. de O. L.; de Macedo, Douglas D. J.; Britto, André (Anais do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD); 2018: Anais do XIX Simpósio em Sistemas Computacionais de Alto Desempenho, 2018)
The increasing number of both digital audio and videos, brings up the necessity of appropriate tools for the storagement and management of those kind of data. As options for the storagement, there are the non-relational databases (NoSQL). The diversity of existing systems provokes the interest in proposing an architecture for the management of that content, in different types of databases. Due to that need, this work proposes the Video7 architecture for storing and retrieving both audio and video streaming files stored in non-relational databases. Based on the architecture, it was implemented a tool that makes use of the Apache HBase, Apache Cassandra, Project Voldemort, Redis and MongoDB databases, and is subjected to stressful routines. The purpose of stress routines is to measure insertion and queries times, in addition to their transfer rates in response to requests to a media server. Redis database presents better performance in the submitted routines, while Project Voldemort and Apache Cassandra perform poorly than other databases.